Cysteine Oxidations in Mitochondrial Membrane Proteins: The Case of VDAC Isoforms in Mammals - Reina, Simona; Pittalà, Maria Gaetana Giovanna; Guarino, Francesca; Messina, Angela; De Pinto, Vito; Foti, Salvatore; Saletti, Rosaria (Frontiers in Cell and Developmental Biology, 2020)
Cysteine residues are reactive amino acids that can undergo several modifications driven by redox reagents. Mitochondria are the source of an abundant production of radical species, and it is surprising that such a large availability of highly reactive chemicals is compatible with viable and active organelles, needed for the cell functions. In this work, we review the results highlighting the modifications of cysteines in the most abundant proteins of the outer mitochondrial membrane (OMM), that is, the voltage-dependent anion selective channel (VDAC) isoforms. This interesting protein family carries several cysteines exposed to the oxidative intermembrane space (IMS). Through mass spectrometry (MS) analysis, cysteine posttranslational modifications (PTMs) were precisely determined, and it was discovered that such cysteines can be subject to several oxidization degrees, ranging from the disulfide bridge to the most oxidized, the sulfonic acid, one. The large spectra of VDAC cysteine oxidations, which is unique for OMM proteins, indicate that they have both a regulative function and a buffering capacity able to counteract excess of mitochondrial reactive oxygen species (ROS) load. The consequence of these peculiar cysteine PTMs is discussed.